2018
DOI: 10.1021/acsenergylett.8b00809
|View full text |Cite
|
Sign up to set email alerts
|

Layered Metal–Organic Framework-Derived Metal Oxide/Carbon Nanosheet Arrays for Catalyzing the Oxygen Evolution Reaction

Abstract: The oxygen evolution reaction (OER) in water splitting plays a critical role in some clean energy production systems. Transition-metal oxides as one of the most common OER electrocatalysts have been widely explored; however, their activity is limited by low electrical conductivity, slow mass transfer, and inadequate active sites. Herein, we develop a feasible strategy in which layered twodimensional metal−organic frameworks (2D MOFs) act as templates to construct metal oxide/carbon (MO x /C, M = Co, Ni, and Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
117
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(117 citation statements)
references
References 44 publications
0
117
0
Order By: Relevance
“…[251][252][253][254] Up to now, various 2D MOF-derived nanostructure arrays have been reported, such as Ni-doped Co-Co 2 N nanosheet/carbon cloth, [255] N-doped carbon-Co 3 O 4 sheet/ carbon cloth, [256] Co 3 O 4 @N-doped carbon nanosheet/nickel foam, [257] and CoSe 2 sheets/carbon cloth. to construct MOF arrays.…”
Section: Synthesis Of Ld Mof Derivativesmentioning
confidence: 99%
“…[251][252][253][254] Up to now, various 2D MOF-derived nanostructure arrays have been reported, such as Ni-doped Co-Co 2 N nanosheet/carbon cloth, [255] N-doped carbon-Co 3 O 4 sheet/ carbon cloth, [256] Co 3 O 4 @N-doped carbon nanosheet/nickel foam, [257] and CoSe 2 sheets/carbon cloth. to construct MOF arrays.…”
Section: Synthesis Of Ld Mof Derivativesmentioning
confidence: 99%
“…Likewise, bimetallic Zn−Cu BTC MOF revealed higher desulfurization capacity than the monometallic Cu‐BTC and even zeolites . Similar studies showed that bimetallic MOF have superior catalytic activities over monometallic MOF being used as heterogeneous catalyst for organic coupling reactions, such as heck reaction, C−H bond halogenation, catalyzing OER reactions, selective oxidation of aromatic substrates, Knoevenagel condensation and Suzuki coupling reaction.,, Besides, some studies have dealt with photocatalytic properties of hybrid MOFs such as Fe/M(M=Mn, Co, Ni) MOFs, Fe(II)@MIL‐100(Fe) and MIL‐53(Fe) MOFs.,, Thus, the rational design and synthesis of hybrid structure with multi‐functionalities could achieve enhanced physicochemical properties and efficiency.…”
Section: Figurementioning
confidence: 70%
“…[9] Likewise, bimetallic ZnÀ Cu BTC MOF revealed higher desulfurization capacity than the monometallic Cu-BTC and even zeolites. [10] Similar studies showed that bimetallic MOF have superior catalytic activities over monometallic MOF being used as heterogeneous catalyst for organic coupling reactions [11,12] such as heck reaction, [13] CÀ H bond halogenation, [14] catalyzing OER reactions, [15] selective oxidation of aromatic substrates, [16] Knoevenagel condensation [17] and Suzuki coupling reaction., [18,19] Besides, some studies have dealt with photocatalytic properties of hybrid MOFs such as Fe/M (M=Mn, Co, Ni) MOFs, Fe(II)@MIL-100(Fe) and MIL-53(Fe) MOFs., [20,21] Thus, the rational design and synthesis of hybrid structure with multi-functionalities could achieve enhanced physicochemical properties and efficiency.Inspired with the possibility to improve the properties through introducing a new metal component in MOF, we hereby report the synthesis and crystal structure of a new bimetallic MOF composed of divalent Zn and trivalent Fe ions linked with 1,4-benzenedicarboxylic (BDC) acid to form FeÀ Zn BDC MOF.The pristine MOF doped or incorporated with another metal provide a scope to tune the electronic band gap. Recent studies show that the incorporation of iron as second metal in MOF decreases the band gap of parent MOF and enhanced its absorption into visible region.…”
mentioning
confidence: 99%
“…Growths of 1D, 2D and 3D MOFs on conducting substrates have also been used as precursors to obtain catalytic active metal oxide composites for water oxidation reaction . Zhou et al .…”
Section: Mofs As Sacrificial Templatesmentioning
confidence: 99%
“…Growths of 1D, 2D and 3D MOFs on conducting substrates have also been used as precursors to obtain catalytic active metal oxide composites for water oxidation reaction. [176,177] Zhou et al had reported that out of the above three crystal morphologies, 2D MOF-derived catalysts outperform those derived from 1D and 3D MOFs. [177] However, since the morphology of the reported MOFs are controlled by selecting different organic ligands (BTC, BDC and DHTP, where DHTP = 2,5-dihydroxyterephthalate, for 1D, 2D and 3D MOFs, respec- tively), the enhancement effects cannot be fully attributed to the morphology of the MOF precursors, because of lacking considerations on chemical reactivity of organic ligands.…”
Section: Design Parameters Of Mof Templatesmentioning
confidence: 99%